Un complemento al teorema de Nyquist - Alvarado Reyes, J.M.; Stern Forgach, C.E. (Revista Mexicana de Física E, 2010)
The content of this article is specially designed for students that are starting their education in data acquisition and signal processing. In some scientific majors this can happen in a compulsory or an elective course or in an experimental one. We review some of the fundamental requirements for proper signal acquisition in order to reconstruct the most important characteristics of the original signal, and at the same time obtain the required resolution when transforming to frequency space. We show that the satisfaction of Nyquist criterion is not sufficient to assure adequate resolution in frequency space. Finally we suggest how to choose the parameters for the best possible acquisition.